IMPACT OF PHOSPHAMIDON AND ITS METABOLITES ON HISTOPATHOLOGY OF THE LIVER, GILL AND INTESTINE OF LABEO - Saharan, Neelam; Dube, K.; Srivastava, P. P.; Prakash, Chandra (Journal of Indian Fisheries Association, 2010)
Impact of phosphamidon, an organophosphorus pesticide and its metabolites viz. dimethyl phosphoric acid and 2-chloro 2-diethyl carbamoylmethyl vinyl acid on histopathology of a common teleost, Labeo rohita was studied by exposing the fish to sub-lethal concentrations which were taken as 1/3rd of LC50 and were equal to 0.0123 ppm for phosphamidon, 0.0160 ppm for dimethyl phosphoric acid and 0.0167 ppm for 2-chloro 2-diethyl carbamoylmethyl vinyl acid respectively. The results revealed that hepatocytes in the liver were markedly swollen and exhibited hydropic degeneration. Fusion of primary lamellae and moderate congestion of blood vessels were evident in the gill. Intestine showed degeneration of mucosa and cellular infiltration in sub-mucosa. LC50 values and histopathological photomicrographs suggest that phosphamidon is more toxic as compared to dimethyl phosphoric and 2-chloro 2-diethyl carbamoylmethyl vinyl acid. Â Key words: Phosphamidon, Metabolites, Histopathology, Labeo rohita. Â